2020
DOI: 10.1002/jmv.25967
|View full text |Cite
|
Sign up to set email alerts
|

Smoking links to the severity of COVID‐19: An update of a meta‐analysis

Abstract: The paper entitled "The impact of COPD and smoking history on the severity of Covid-19: A systemic review and meta-analysis." published in Journal of Medical Virology on 15 April, 2020 1 . The results revealed the pooled OR of COPD and the development of severe , while the OR of ongoing smoking was 1.98 (Fixed effect model, 95% CI: 1.29-3.05). However, in the sensitivity analysis, by excluding each study one by one showed that the study from W. Guan 2 was a major source of heterogeneity.After excluding this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 9 publications
1
40
0
3
Order By: Relevance
“…According to the prespecified enrolment plan and matching strategy (Supplementary material), 158 controls matched for age and sex with the 79 Covid-19 cases were enrolled. When this analysis was carried out, 9 out of the 79 cases (11.4%) died 20 [12][13][14][15][16][17][18][19][20][21][22][23][24] days after hospitalization, 38 (48.1%) were discharged after 23 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] males, p = 0.92) and body mass index. Cases were less likely ever smokers than controls (22.8% vs 45.6%, p = 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…According to the prespecified enrolment plan and matching strategy (Supplementary material), 158 controls matched for age and sex with the 79 Covid-19 cases were enrolled. When this analysis was carried out, 9 out of the 79 cases (11.4%) died 20 [12][13][14][15][16][17][18][19][20][21][22][23][24] days after hospitalization, 38 (48.1%) were discharged after 23 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] males, p = 0.92) and body mass index. Cases were less likely ever smokers than controls (22.8% vs 45.6%, p = 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of clarity on the issue is likely because there has been a lower than expected prevalence of smoking reported in retrospective and observational databases because of incomplete reporting of smoking status in patients in emergency situations. Therefore, some studies reported no increase in smoking-related disease whereas more in depth analyses of demographic data showed an increased risk of severe associated with smoking (Guo, 2020) (Vardavas and Nikitara, 2020) (Zhao et al, 2020). A recent study showed that smoking is a risk factor for more severe COVID-19 among young adults (Adams et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis factors of COVID-19 patients include age, [ 50 , 58 ] sex, [ 50 , 58 ] obesity, [ 59 ] smoking, [ 55 , 60 – 62 ] C-reactive protein (CRP), D-dimer, and lymphocyte count. [ 50 ]…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…[ 59 ] As for smoking, it is very likely to be related to the negative progression and adverse consequences of COVID-19. [ 55 , 60 – 62 ]…”
Section: Prognostic Factorsmentioning
confidence: 99%